Comparison of granisetron and lidocaine on reducing injection pain of etomidate: a controlled randomized study - Saliminia,Alireza (2017)
Abstract Background and objectives Reducing pain on injection of anesthetic drugs is of importance to every anesthesiologist. In this study we pursued to define if pretreatment by granisetron reduces the pain on injection of etomidate similar to lidocaine. Methods Thirty patients aged between 18 and 50 years of American Society of Anesthesiologists physical status class I or II, whom were candidates for elective laparoscopic cholecystectomy surgery were enrolled in this study. Two 20 gauge cannulas were inserted into the veins on the dorsum of both hands and 100 mL of normal saline was administered during a 10 min period from each cannula. Using an elastic band as a tourniquet, venous drainage of both hands was occluded. 2 mL of granisetron was administered into one hand and 2 mL of lidocaine 2% at the same time into the other hand. One minute later the elastic band was opened and 2 mL of etomidate was administered to each hand with equal rates. The patients were asked to give a score from 0 to 10 (0 = no pain, 10 = severe pain) to each the pain sensed in each hand. Results Two patients were deeply sedated after injection of etomidate and unable to answer any questions. The mean numerical rating score for injection pain of intravenously administered etomidate after intravenous granisetron was 2.3 ± 1.7, which was lower when compared with pain sensed due to intravenously administered etomidate after administration of lidocaine 2% (4.6 ± 1.8), p < 0.05. Conclusion The result of this study demonstrated that, granisetron reduces pain on injection of etomidate more efficiently than lidocaine.